2013
DOI: 10.1134/s1068162013050117
|View full text |Cite
|
Sign up to set email alerts
|

Calpain system dysregulation in rat brain at beta-amyloid-induced neurodegeneration

Abstract: Experimental evidences of calcium-dependent proteolysis dysregulation in brain of murine model of Alzheimer disease were obtained. Experimental treatment consisted in intra-hippocampal injection of amyloid beta-peptide (AP1-40) promoted activation of main calpain forms in murine brain along with decrease incontent of natural calpain inhibitor, calpastatin. As a result of prognostic experiment on the correction of neurodegeneration induced in murine the neuroprotective properties of steroid hormone estradiol we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In addition, the neuroprotective role of estrogen has recently been tested specifically against amyloid toxicity by using an Alzheimer’s disease rat model, which is produced by intra-hippocampal Aβ140 injection. 109 Aβ140 treatment has been shown to cause at least two times more calpain activation in the cerebral cortex, suggesting a role for calpains in amyloid toxicity. However, introduction of estrogen has been demonstrated to reduce Aβ140 peptide levels in rat brain, and it has also been demonstrated that rats on estrogen therapy have not developed a behavioral dysfunction.…”
Section: Neuroprotection Through Estrogen Receptorsmentioning
confidence: 99%
“…In addition, the neuroprotective role of estrogen has recently been tested specifically against amyloid toxicity by using an Alzheimer’s disease rat model, which is produced by intra-hippocampal Aβ140 injection. 109 Aβ140 treatment has been shown to cause at least two times more calpain activation in the cerebral cortex, suggesting a role for calpains in amyloid toxicity. However, introduction of estrogen has been demonstrated to reduce Aβ140 peptide levels in rat brain, and it has also been demonstrated that rats on estrogen therapy have not developed a behavioral dysfunction.…”
Section: Neuroprotection Through Estrogen Receptorsmentioning
confidence: 99%